Dynamics of Islamic Family Law "Husband Accuses Wife of Adultery Without Evidence and Witnesses (Sumpah Lian) Imam Abu Hanifah's Perspective" - Huzaini, Huzaini (Assyfa Journal of Islamic Studies, 2023)
In the household, it cannot be denied that sometimes husbands are suspicious or accuse their wives of committing adultery without any evidence or witnesses. Islam overcomes these problems in a lean way. Abu Hanifah is a scholar who prioritizes using ro'yu in solving problems. According to Abu Hanifah's thoughts, heading to Abu Hanifah's thoughts, the problem in this research and what legal distinct method Abu Hanifah uses in resolving the Lian problem. This research is a character study research, namely library research. The data sources in this research are secondary data, namely primary data and supporting data. This research was analyzed and concluded with general data. Qualitative descriptive, namely, the author also provides a widespread and systematic, factual and accurate description of Lian by researching and discussing existing data. Content analysis is the method used to analyze the data that has been presented and finally reach a conclusion. The results of this research are that the impact of Lian on marriage, according to Abu Hanifah's thoughts, is that if Lian has occurred, then the husband can still return to his wife; the wife's prohibition on the husband is only temporary, not forever, or Lian is seen as divorce, not fasakh. Until it is known who is lying between the two, then it is haram forever. The legal istinbat method used by Abu Hanifah in the Lian matter refers to the generality of the verse, namely the verse about divorce. According to Abu Hanifah, the Lian problem is a form of divorce.